2004
DOI: 10.1007/s00415-004-0333-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parkinson?s disease and other types of Parkinsonism

Abstract: These prevalence rates are similar than those found in studies made in other European countries. The prevalence of both Parkinson's disease and other types of parkinsonism increased with age, with no significant differences between men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 20 publications
3
18
0
3
Order By: Relevance
“…Generally, PD is rare before age 60 (0.13%‐1.6%), increases with age, and can reach a maximum of 9% among people aged 80‐84. Thereafter (85‐89), prevalences decline and vary from 0.87% to 3.6% 3, 4, 5, 6, 7, 8, 9, 10. Incidence rates are also low for those aged 50‐59 and increase sharply afterward.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PD is rare before age 60 (0.13%‐1.6%), increases with age, and can reach a maximum of 9% among people aged 80‐84. Thereafter (85‐89), prevalences decline and vary from 0.87% to 3.6% 3, 4, 5, 6, 7, 8, 9, 10. Incidence rates are also low for those aged 50‐59 and increase sharply afterward.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies estimate its prevalence to be 1.5% in persons older than 65 years [1]. Its clinical manifestations include 4 cardinal signs: tremor, rigidity, bradykinesia and postural instability.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review comprised 44 studies estimating prevalence or incidence rates of PD of which 21 studies reported age- and gender-specific prevalence as well as the size of the underlying population [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. To supplement these data by studies that were published after 2004, an additional systematic literature search was performed using the same search strategy as described by von Campenhausen et al [10] (Fig.…”
Section: Methodsmentioning
confidence: 99%